Magnetic Resonance Imaging of Thumb Carpometacarpal Arthroplasty: Preoperative Evaluation and Postoperative Imaging - Lemos, Diego F.; Kanner, Christopher D.; Geeslin, Matthew G.; Lack, Mark E.; Benoit, Michel Y.; Alaia, Erin F. (Seminars in Musculoskeletal Radiology, 2025)
In this review we discuss the magnetic resonance imaging (MRI) appearance of thumb carpometacarpal (CMC) arthroplasty, both the preoperative evaluation and particularly the postoperative MRI of different surgical options for patients with advanced degenerative disease of the basal joint of the thumb. The first CMC joint is one of the most frequently involved articulations in the hand and wrist in the setting of degenerative osteoarthrosis and certainly a pain generator and important cause of disability due to its significant impact on hand function. It is the most common joint for which surgery is sought in the wrist. Radiologists interpreting imaging studies of patients with first CMC joint arthroplasty must be familiar with the normal and abnormal preoperative appearance of the thumb basal joint. Moreover, knowledge of the normal postoperative MRI findings, as well as the appearance of patterns of failure and complications, is of paramount importance.
Keywords: arthroplasty; ligament reconstruction-tendon interposition; suspensionplasty